2017
DOI: 10.1152/ajpregu.00512.2016
|View full text |Cite
|
Sign up to set email alerts
|

Adverse metabolic phenotype of female offspring exposed to preeclampsia in utero: a characterization of the BPH/5 mouse in postnatal life

Abstract: Preeclampsia (PE) is a devastating disorder of pregnancy that classically presents with maternal hypertension and proteinuria after 20 wk of gestation. In addition to being a leading cause of maternal and fetal morbidity/mortality, epidemiological and prospective studies have revealed long-term consequences for both the mother and baby of preeclamptic pregnancies, including chronic hypertension as well as other cardiovascular diseases and metabolic derangements. To better understand the effect of in utero expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(80 citation statements)
references
References 33 publications
7
68
0
1
Order By: Relevance
“…Ongoing investigations seek to identify the cell types contributing to aberrant gene expression in the BPH/5 decidua. Further, recently published data from the Sones laboratory demonstrated that BPH/5 female mice have an adverse metabolic phenotype from early adulthood, which includes hyperphagia and obesity with increased white adipose tissue (WAT), proinflammatory reproductive WAT, and leptin resistance (63). Obesity before and at the time of conception has been linked to adverse pregnancy outcomes (64, 65).…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing investigations seek to identify the cell types contributing to aberrant gene expression in the BPH/5 decidua. Further, recently published data from the Sones laboratory demonstrated that BPH/5 female mice have an adverse metabolic phenotype from early adulthood, which includes hyperphagia and obesity with increased white adipose tissue (WAT), proinflammatory reproductive WAT, and leptin resistance (63). Obesity before and at the time of conception has been linked to adverse pregnancy outcomes (64, 65).…”
Section: Discussionmentioning
confidence: 99%
“…Continued studies by this group evaluated the transcriptome at E7.5 implantation sites and E10.5 placenta demonstrating significant upregulation of C3 gene expression and reinforcing the importance of the complement system in the placental pathology [50]. The most recent study from this group [51] characterized the metabolic phenotype of offspring of the BPH/5 mouse and demonstrated the long-term consequences that accompany the adverse complement activation early in pregnancy.…”
Section: The Complement System In Stage 1 Of Placental Preeclampsiamentioning
confidence: 99%
“…Throughout all experiments, mice were fed ad libitum standard 5001 chow. Pair-feeding of nonpregnant BPH/5 female mice was done as previously described [17] by feeding the same amount of normal chow to BPH/5 as consumed by age-matched C57 female mice for 2 weeks. Intrastrain timed matings with day of vaginal plug detection denoted as e0.5 were performed with BPH/5 pair-feeding, beginning at e0.5 and continuing for 7 days until the mice were sacrificed, as previously described [14].…”
Section: Animalsmentioning
confidence: 99%